2016
DOI: 10.1080/14767058.2016.1228053
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress equilibrium during obstetric event in normal pregnancy

Abstract: We demonstrated that MDA concentrations are increased two hours after obstetric event, and this increase correlates with VD. The TAC was increased as a compensatory mechanism during obstetric event. Another important finding is that women receiving analgesia administration in VD, as well as dexamethasone administration in caesarean section, experienced a protector effect that decreased MDA levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The first major finding of this study is that pregnancy is accompanied by highly significant changes in O & NS as indicated by increased AOPP and NOx and lowered TRAP and -SH levels findings, which are in agreement with previous reports (Choi et al, 2002;De Lucca et al, 2016;Fialová et al, 2003;Kalousová et al, 2002;Salas-Pacheco et al, 2016). In normal pregnancy, there is an increase in Table 2 Results of multivariate GLM analyses with the 7 oxidative and nitrosative stress and antioxidant biomarkers as dependent variables and pregnancy, clinical depression diagnoses, age and PON1 genotypes as explanatory variables.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The first major finding of this study is that pregnancy is accompanied by highly significant changes in O & NS as indicated by increased AOPP and NOx and lowered TRAP and -SH levels findings, which are in agreement with previous reports (Choi et al, 2002;De Lucca et al, 2016;Fialová et al, 2003;Kalousová et al, 2002;Salas-Pacheco et al, 2016). In normal pregnancy, there is an increase in Table 2 Results of multivariate GLM analyses with the 7 oxidative and nitrosative stress and antioxidant biomarkers as dependent variables and pregnancy, clinical depression diagnoses, age and PON1 genotypes as explanatory variables.…”
Section: Discussionsupporting
confidence: 93%
“…Pregnancy is accompanied not only by increased immune activation (Anderson and Maes, 2013) and consequent TRYCAT pathway activation (Anderson and Maes, 2013), but also O & NS as indicated by increased lipid peroxides (Patil et al, 2006;Walsh, 1994), production of NO metabolites (NOx) (Choi et al, 2002) and AOPP levels (Fialová et al, 2003;Kalousová et al, 2002). Antioxidant defenses are lowered during pregnancy as indicated by lowered PON1 (Rojekar and Mogarekar, 2015), TRAP (Salas-Pacheco et al, 2016), -SH (De Lucca et al, 2016) and zinc (Ma et al, 2015;Nossier et al, 2015;Tabrizi and Pakdel, 2014) levels as well as other antioxidants (Salas-Pacheco et al, 2016). Increased peripheral inflammation and O & NS have been demonstrated to be associated with various obstetric complications, including preeclampsia (Kirbas et al, 2016;Ma et al, 2015;Nossier et al, 2015), glucose intolerance (Zein et al, 2016), miscarriage, fetal anomaly and growth restriction and preterm labor (Duhig et al, 2016;Mukhopadhyay et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal plants affect the human body as a result of various chemical compounds, and one type of influence is anti-oxidative interaction [87][88][89][90][91][92][93][94]. As energy consumption increases during pregnancy, and lactation encourages the formation of free radicals in a woman's body, investigating their antioxidant qualities is warranted [95][96][97][98][99][100]. The presence of phenols and flavonoids in plant extracts has been linked to its antioxidant activity.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…During the process of labor, the intensity of uterine contractions increases uterus pressure and can cause interruption or reduction in the uteroplacental blood flow, causing cycles of cellular hypoxia and reoxygenation. These events of parturition are responsible for inducing increased oxidative stress in pregnant women, which must be controlled by their antioxidant system [40,41].…”
Section: Pregnancy Maternal Immunity and Oxidative Stressmentioning
confidence: 99%